Effects of prostaglandin on fracture healing: An experimental study on rabbits - MAITI, S K; HOQUE, M; AITHAL, H P; SINGH, G R; KALICHARAN, KALICHARAN (The Indian Journal of Animal Sciences, 2014)
The effect of locally administered prostaglandin (PGE2) on fracture healing was studied in 8 adult New Zealand White rabbits divided equally in 2 groups. In all animals, midshaft transverse fracture of both the ulnae was created under thiopental (2.5%) anaesthesia. In test group, 0.1 rol (25 Âµg)prostaglandin was injected at fracture site on alternate day for 30 postoperative days. Radiographs taken immbdiately and on days 10, 20, 30 and 40 postoperatively. In test group (A), periosteal proliferation started as early as on day 10 postoperatively and complete obliteration offracture gap was observed on day 30. Remodelling of bridging callus and well developed periosteal continuity were observed on day 40 PO. Whereas in control group, fracture healing was comparatively slow, delayed and the defect site was well visible till day 40 PO. Histopathological observations further confirmed the radiological findings. No physiological side effects and other complications were observed in any group.